Efeito da realcalinização química e eletroquímica com soluções de Koh e NA2CO3 no desenvolvimento de reação álcali-agregado em concretos de cimento Portland. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The corrosion of the steel embedded in reinforced concrete is one of the main pathological manifestations identified in structures and recovery techniques such as chemical and electrochemical realkalinization have been used as prevention or recovery measures. It happens that the alkali-silica reaction as a side effect of realkalinization has not been widely understood. This work aims to fill this knowledge gap. As the realkalinization treatment is intended to increase the pH and incorporate alkali into the concrete, this procedure can increase the likelihood of manifesting reactions between the alkali and siliceous aggregates, in order to evaluate this possible side effect, concrete specimens were cast with potentially reactive and potentially harmless aggregates These were subjected to carbonation and chemical and electrochemical realkalinization in potassium hydroxide and sodium carbonate solutions. Different solutions were chosen with the intention of comparing their efficiencies in the treatments and to verify their behavior regarding the development of AAR. For the collection of evidence, tests of corrosion potential, scanning electron microscopy, optical microscopy, EDS, XRD and XRF were used. With the corrosion potential, it was possible to analyze whether the reference, carbonated and realkalinized concretes had a high or low probability of corrosion, and to verify the efficiency of the treatments in reducing the probability of corrosion after their performance. By means of the phenolphthalein indicator in the concrete, it was possible to observe the realkalinization and by visual analysis it was noticed a decrease in the corrosion of the reinforcement when compared to the carbonated concretes that were not treated. The images in electron and optical microscopy allowed to verify the degradation of the aggregates and the appearance of gel on their surface, characteristic effects of alkali-silica reaction, mainly in reactive aggregates and in concretes treated with electrochemical realkalinization, possibly due to the electrolysis of water in the proximities of the reinforcement, forming hydroxyls, which attack the siliceous aggregates. With the present work, it was possible to bring more data from the electrochemical treatment, regarding its efficiency and durability, and evidence of the possible appearance of alkali-silica reactions due to realkalinization treatments, showing that this side effect cannot yet be disregarded.
Keywords: reação álcali-sílica; reação álcali-agregado; realcalinização química; realcalinização eletroquímica; carbonatação; corrosão; concreto; alkali-silica reaction; alkali-aggregate reaction; chemical realkalisation; electrochemical realkalisation; carbonation; corrosion; concrete; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA